Beyond Calories: A Holistic Assessment of the Global Food System - Ritchie, Hannah; Reay, David S.; Higgins, Peter (Frontiers in Sustainable Food Systems, 2018)
The global food system is failing to meet nutritional needs, with growing concerns for health related to both under-, over-consumption and severe micronutrient deficiency. The 2nd Sustainable Development Goal (SDG2) targets the end of malnutrition in all forms by 2030. To address this challenge, the focus around food security and malnutrition must be broadened beyond the scope of sufficient energy intake to take full account of total nutrient supply and requirements. Here, for the first time, we have quantitatively mapped the global food system in terms of energy, protein, fat, essential amino acids, and micronutrients from 'field-to-fork', normalised to an equitable per capita availability metric. This framework allows for the evaluation of the sufficiency of nutrient supply, identifies the key hotspots within the global food supply chain which could be targeted for improved efficiency, and highlights the trade-offs which may arise in delivering a balanced nutritional system.